A new species of the genus Euthystiroides Zhang, Zheng & Ren, 1995 fromHeilongjiang, China (Orthoptera, Acridoidea, Acrididae) - Li, Guochao; Wen, Xiaochen; Zhi, Yongchao (Zootaxa, 2020)
A new species of the genus Euthystiroides Zhang, Zheng & Ren, 1995 i.e. Euthystiroides heilongjiangensis sp. nov is described from Heilongjiang, China. The new species is allied to E. dalianensis Zhang, Zheng & Ren, 1995, but differs from latter by head shorter than pronotum distinctly and without black stripe in the middle, tegmina of male narrower, length 4.0 times width; length of interspace 1.9 times minimum width in mesosternum and width of epiphallus almost equal to high.